"Neo4j and Amazon Neptune: Top Graph Databases in Medical Insurance" - Yogesh Jaiswal Chamariya (Educational Administration: Theory and Practice, 2021)
In recent years, the medical insurance sector has experienced a surge in the use of graph databases to enhance data management, relationship modeling, and analytics. Two dominant players in this field are Neo4j and Amazon Neptune, which offer powerful graph database solutions designed to meet the complex needs of the medical insurance industry. This paper explores the capabilities, advantages, and applications of Neo4j and Amazon Neptune in medical insurance, examining their ability to manage intricate relationships, improve fraud detection, optimize claims processing, and enhance customer experience. Through comparative analysis, we highlight how these graph databases are transforming the medical insurance landscape.